5‐/12‐Lipoxygenase‐linked cascade contributes to the IL‐33‐induced synthesis of IL‐13 in mast cells, thus promoting asthma development. Issue 2 (8th September 2017) - Ro, MyungJa; Lee, A‐Jin; Kim, Jae‐Hong
Abstract: Background: As asthma progresses, the levels of IL‐33 in serum are markedly increased and contribute to asthmatic development and exacerbation. Mast cells, one of the principal effector cells in the pathogenesis of asthma, express high levels of the IL‐33 receptor ST2 and have been shown to be activated by IL‐33. Thus, IL‐33 stimulates mast cells to produce Th2‐type cytokines such as IL‐13, thus contributing to asthmatic development. However, the signaling mechanism for IL‐33‐induced synthesis of Th2 cytokines, particularly IL‐13, has not been fully elucidated in mast cells. Methods: The role of 5‐ or 12‐LO in the IL‐33‐induced synthesis of IL‐13 was investigated using knockdown or pharmacological inhibitors in bone marrow‐derived mast cells (BMMCs) and animal model. Results: Blockade of 5‐ or 12‐LO significantly suppressed IL‐33‐induced synthesis of IL‐13 in BMMCs. The subsequent action of 5‐ and 12‐LO metabolites through their specific receptor, BLT2, was also critical for IL‐33‐induced synthesis of IL‐13. We also demonstrated that the MyD88‐p38 kinase cascade lies upstream of 5‐/12‐LO and that NF‐κB lies downstream of 5‐/12‐LO to mediate the IL‐33‐induced synthesis of IL‐13 in mast cells. Consistent with these findings, we observed that in an IL‐33‐administered asthmatic airway inflammation model, IL‐13 levels were markedly increased in bronchoalveolar lavage fluid, but its levels were markedly suppressed by treatment with inhibitors of 5‐LO, 12‐LO or BLT2, further suggesting roles of 5‐/12‐LO in IL‐33‐induced IL‐13 production. Conclusion: Our results suggest that "MyD88‐5‐/12‐LO‐BLT2‐NF‐κB" cascade significantly contributes to the IL‐33‐induced synthesis of IL‐13 in mast cells, thus potentially contributing to asthmatic development and exacerbation.